LINGUISTIC PECULIARITIES OF EFFECTIVE PUBLIC SPEECH - Vidmanė Žoštautaitė; Dinalda Simuntienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2022)
Public speaking comes in many different forms and has many uses but the main aim is to inform, educate and successfully influence the public with motivational and powerful statements. The majority of public speakers that an individual might encounter are political figures. In order to demonstrate competence and credibility, they evoke different language techniques. Carefully chosen type of speech (demonstrative, informative, ceremonial or persuasive) alongside with particular linguistic devices (lexical and stylistic) allow any influential orator to create a notable impact on the target audience and manipulate the mind-set of the masses. The purpose of the research was to unveil the effectiveness of linguistic devices used in the speeches of three US presidents, to compare as well as to indicate the predominant lexical and stylistic means that ensure oratory success. The methods of theoretical analysis and descriptive comparative linguistic analysis were applied. 45 lexical devices were identified while analysing the speeches, out of which 23 were chosen for a more thorough examination. 162 stylistic devices were identified and 45 of them were analysed in the research. The article reveals that lexical means create a more cohesive but less creative speech, whereas stylistic devices serve to reflect the speakers’ idiosyncrasy. The speeches of Barack Obama, Joe Biden sound clear and knowledgeable, whereas Donald Trump creates a sense of informality, forcefulness or even aggressiveness.